2009
DOI: 10.1063/1.3088862
|View full text |Cite
|
Sign up to set email alerts
|

Low threshold current density of InAs quantum dash laser on InP (100) through optimizing double cap technique

Abstract: International audienceWe report on the uniformity improvement of InAs quantum dashes (QDHs) grown by molecular beam epitaxy on InP (100) through optimizing double cap technique. Broad-area lasers were fabricated with an emission wavelength of 1.58 μm. A threshold current density of 360 A/cm2 was achieved for a five stack QDH structure and a cavity length of 1.2 mm. This results from a reduced inhomogeneous broadening (62 meV) and lower internal optical losses (7 cm-1). The achievement paves the way toward ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…30(a). The optimized double capping technique, primarily developed for the InAs/InP Qdots growth (discussed in section 2.2), was also employed by Zhou et al [6,7] to obtain homogeneous Qdashes and to tune the emission wavelength of a single and multi-stack InAs/InGaAsP Qdash structures on (100)InP substrate. By selecting a thin 2.2 nm first capping layer and short 30 s growth interruption time, they measured a room temperature PL linewidth of 60 meV from 5 stacked Qdash structure (TN-S) centered at 1.55 µm, shown in Figs.…”
Section: Qdashes On (100) Inp Substratementioning
confidence: 99%
See 1 more Smart Citation
“…30(a). The optimized double capping technique, primarily developed for the InAs/InP Qdots growth (discussed in section 2.2), was also employed by Zhou et al [6,7] to obtain homogeneous Qdashes and to tune the emission wavelength of a single and multi-stack InAs/InGaAsP Qdash structures on (100)InP substrate. By selecting a thin 2.2 nm first capping layer and short 30 s growth interruption time, they measured a room temperature PL linewidth of 60 meV from 5 stacked Qdash structure (TN-S) centered at 1.55 µm, shown in Figs.…”
Section: Qdashes On (100) Inp Substratementioning
confidence: 99%
“…However, the significant reduction of size and shape dispersion (large inhomogeneous broadening) of these nanostructures due to selfassemble growth procedure still pose a challenge in achieving high quality epitaxial material and device performance. Currently, the size dispersion, characterized in terms of photoluminescence (PL) linewidth (full-width-at-half-maximum, FWHM), are ~20 meV at 10 K for Qdots [4] and ~50 meV at room temperature for Qdashes [5][6][7]. These values indicate further improvement is required to make it as competitive as the matured InAs/GaAs Qdots on GaAs substrate technology [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to the static performance characteristics, Zhou et al [49,50] reported the smallest value of threshold current density (72 A/cm 2 per layer) and transparency current density (45 A/cm 2 per layer) on a InAs/InGaAsP Qdash material system. The 5-stack Qdash-in-barrier SCH laser structure was grown through the optimized double-cap technique, and employing a 2.2 nm cap with a 30-s growth interruption.…”
Section: Inas/ingaasp/inp Qdash Lasersmentioning
confidence: 99%
“…Such nanostructures can be grown using solid-source molecular beam epitaxy ͑MBE͒, 2 gas-source MBE, [3][4][5] or metal-organic vapor-phase epitaxy ͑MOVPE͒. 6,7 For nanostructure formation, the InAs material can be deposited directly on the InP substrate.…”
Section: Introductionmentioning
confidence: 99%